Privacy Protection in Bigdata: A Survey - et. al., Saumya Gupta, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Bigdata becomes a significant sector and academics research topic. Bigdata is a two-edged sword. The rising volume of information together will increase the likelihood of blundering non-public data privacy. Due to many new technologies and innovations that pervade our everyday lives, like smartphones and social networking apps, and the Internet of Things-based intelligent-world systems, the large amount of data generated in our world has exploded. During this data processing, storage, and the use of the information it can quickly cause personal information exposure and the difficulty of interpreting the information. The aim is to incorporate this range of information into one framework for big data management and to recognize problems regarding privacy. This paper begins with the introduction of bigdata, its process, protection issues, and tools which are used to solve its problems